Determinants of Symptomatic Vulvovaginal Candidiasis among Human Immunodeficiency Virus Type 1 Infected Women in Rural KwaZulu-Natal, South Africa - Teke Apalata; William H. Carr; Willem A. Sturm; Benjamin Longo-Mbenza; Prashini Moodley (Hindawi Limited, 2014)
Introduction. We sought to determine the association between HIV-induced immunosuppression, virologic correlates, and vulvovaginal candidiasis (VVC). Methods. This is a retrospective cohort study, where HIV infected and uninfected women were studied with VVC being the primary outcome. Ninety-seven HIV-infected and 101 HIV-uninfected women were enrolled between June and December 2011. Cases of VVC were confirmed. HIV RNA load was determined by RT-PCR and CD4 counts were obtained from medical records. Results. Fifty-two of 97 (53.6%) HIV-infected and 38/101 (37.6%) HIV-uninfected women were diagnosed with VVC (P=0.032). The relative risk for VVC amongst HIV-infected patients was 1.53 (95% CI: 1.04-2 P=0.024). Cases of VVC increased at CD4+ T cell count below 200 cells/mm3 (P<0.0001) and plasma HIV RNA load above 10 000 copies/mL (P<0.0001). VVC was associated with increased genital shedding of HIV (P=0.002), and there was a linear correlation between plasma HIV load and genital HIV shedding (r=0.540; R2=0.292; P<0.0001). Women on HAART were 4-fold less likely (P=0.029) to develop VVC. Conclusion. CD4 counts below 200 cells/mm3 and plasma HIV loads ≥10 000 copies/mL were significantly associated with VVC.